2022
DOI: 10.3390/cancers14040910
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing SLAMF3 Expression Restores Sorafenib Response in Hepatocellular Carcinoma Cells through the Induction of Mesenchymal-to-Epithelial Transition

Abstract: Background: Acquired resistance to sorafenib in hepatocellular carcinoma (HCC) patients results in poor prognosis. Epithelial-to-mesenchymal transition (EMT) is the major mechanism implicated in the resistance to sorafenib. We have reported the tumor suppressor role of SLAMF3 (signaling lymphocytic activation molecules family 3) in HCC progression and highlighted its implication in controlling the MRP-1 transporter activity. These data suggest the implication of SLAMF3 in sorafenib resistance mechanisms. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that ABC transporters play a central role in sorafenib resistance [39]. Indeed, different pumps, including MDR1, MRP1, MRP2, MRP3, and BCRP, have been reported to export the anticancer drug from cells, and thus are associated with sorafenib resistance [49][50][51]. In this landscape, we decide to investigate the effect of caryophyllane sesquiterpenes towards MDR1, MRP1, and MRP2 pumps based on the results obtained in our previous work, which highlighted a lower effect of these compounds on MRP3 transporter [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that ABC transporters play a central role in sorafenib resistance [39]. Indeed, different pumps, including MDR1, MRP1, MRP2, MRP3, and BCRP, have been reported to export the anticancer drug from cells, and thus are associated with sorafenib resistance [49][50][51]. In this landscape, we decide to investigate the effect of caryophyllane sesquiterpenes towards MDR1, MRP1, and MRP2 pumps based on the results obtained in our previous work, which highlighted a lower effect of these compounds on MRP3 transporter [20].…”
Section: Discussionmentioning
confidence: 99%
“…SFRs can work in combination with the CD47 pathway but function independently of CD47 to mitigate macrophage phagocytosis. 163 SLAMF3 is also expressed in cancer cells, 164 but its function in phagocytosis in cancer immunotherapy remains unclear.…”
Section: Gd2mentioning
confidence: 99%
“…Therefore, researchers investigated the induction of ferroptosis in HCC cells. Sorafenib is currently used as the first-line drug for the treatment of advanced HCC, and studies have shown that it could induce ferroptosis of HCC cells and thereby inhibit their proliferation ( 18 ). And the efficacy of sorafenib was affected by intracellular genetic status; for example, Rb-negative hepatoma cells were more sensitive to sorafenib-induced ferroptosis ( 19 ).…”
Section: The Role Of Ferroptosis In Liver Diseasesmentioning
confidence: 99%